MEDIA LITERACY TRAINING FOR SENIOR HIGH SCHOOL STUDENTS IN MEDAN CITY - Mazdalifah; Lubis, Fatma Wardy; Sitepu, Yovita Sabarina (Talenta Publisher, 2018)
The phenomenon of internet use, especially social media among teenagers in high school students shows an increase. Some cases show up such as: cyberbullying, trafficking, hoaxes and hate speech. The purpose of community service is to prepared high school students have knowledge and skills in internet media literacy, especially social media. The training participants numbered 42 people, consisting of: SMA N 1, SMA N 2, SMA Harapan Mandiri, SMA Harapan 3, and SMA Bimsa Medan. Form of community service activities by mapping problems through Focus Group Discussion (FGD). Then do the training for two days. The results of the FGD and Seminar shows that the use of the internet, especially social media, includes a very high category of six hours per day. The most widely accessed social media are Instagram and Whatsapp. The purpose they access is to find out information about friends, celebrities, and activities / events that happening around them. Generally high school students have made efforts to choose good media content and avoid bad content, such as violence and pornography. High school students try to read messages on social media well and think about what will be written. They do things like this to avoid the law as stated in the Indonesia ITE Law.